The NE Lau Basin: Widespread and Abundant Hydrothermal Venting in the Back-Arc Region Behind a Superfast Subduction Zone - Baker, Edward T.; Walker, Sharon L.; Massoth, Gary J.; Resing, Joseph A. (Frontiers in Marine Science, 2019)
The distribution of hydrothermal venting reveals important clues about the presence of magma in submarine settings. The NE Lau Basin in the southwest Pacific Ocean is a complex back-arc region of widespread hydrothermal activity. It includes spreading ridges, arc volcanoes, and intra-plate volcanoes that provide a perhaps unique laboratory for studying interactions between hydrothermal activity and magma sources. Since 2004, multiple cruises have explored the water column of the NE Lau Basin. Here we use these data to identify and characterize 43 active hydrothermal sites by means of optical, temperature, and chemical tracers in plumes discharged by each site. Seventeen of 20 prominent volcanic edifices dispersed among the Tofua arc, spreading ridges, and plate interiors host active hydrothermal sites. Fourteen apparently discharge high-temperature fluids, including a multi-year submarine eruption at the intra-plate volcano W Mata. The 430 km of spreading ridges host 31 active sites, one an eruption event in 2008. Our data show that the relationship between site spatial density (sites/100 km of ridge crest) and ridge spreading rate (8-42 mm/yr) in the NE Lau Basin follows the same linear trend as previously established for the faster-spreading (40-90 mm/yr) ridges in the central Lau Basin. The lower site density in the NE Lau Basin compared to the central Lau is consistent with recent plate reconstructions that more than halved earlier estimates of ~50-100 mm/yr spreading rates in the NE Lau Basin. Combined data from the spreading ridges throughout the entire Lau back-arc basin demonstrates that hydrothermal sites, normalized to spreading rate, are ~10× more common than expected based on existing mid-ocean ridge data. This increase documents the ability of meticulous exploration, using both turbidity and chemical sensors, to more fully describe the true hydrothermal population of a spreading ridge, compared to conventional techniques. It further reveals that the Lau back-arc basin, benefiting from both ridge and arc magma sources, supports an exceptionally high population of ridge and intra-plate hydrothermal sites.